2017
DOI: 10.1021/acs.est.7b02382
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Oxide Embedded Nitrogen Self-Doped Biochar Composites: Fast and High-Efficiency Adsorption of Heavy Metals in an Aqueous Solution

Abstract: Lead (Pb) pollution in natural water bodies is an environmental concern due to toxic effects on aquatic ecosystems and human health, while adsorption is an effective approach to remove Pb from the water. Surface interactions between adsorbents and adsorbates play a dominant role in the adsorption process, and properly engineering a material's surface property is critical to the improvement of adsorption performance. In this study, the magnesium oxide (MgO) nanoparticles stabilized on the N-doped biochar (MgO@N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(99 citation statements)
references
References 62 publications
1
98
0
Order By: Relevance
“…In a study about magnetic biochar for mercury removal, it was found that Fe 3+ in tetrahedral coordination contributes to mercury adsorption on the biochar (Yang et al 2016b). For the sorption of some heavy metals, ion exchange may also play an important role in the sorption of biochar (Ling et al 2017).…”
Section: Sorption Of Biocharmentioning
confidence: 99%
“…In a study about magnetic biochar for mercury removal, it was found that Fe 3+ in tetrahedral coordination contributes to mercury adsorption on the biochar (Yang et al 2016b). For the sorption of some heavy metals, ion exchange may also play an important role in the sorption of biochar (Ling et al 2017).…”
Section: Sorption Of Biocharmentioning
confidence: 99%
“…Modified biochar produced with acid, base, and oxidation treatment that supported zero-valent iron nanoparticles improved the removal of Cr(VI) using acid treated biochar, owing to the large surface area, low surface negative charge, and low pH [148]. Magnesium oxide nanoparticles stabilized on N-doped biochar synthesized by fast pyrolysis (400-600°C) resulted in a high Pb adsorption capacity in short equilibrium time (<10 min) and a large material through the system including removal of Cd 2+ and tetracycline [149]. Modified biochar through activation has demonstrated great sorption efficiency of HMs.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…Modified biochar with magnet (hematite) and NaOH are cheap sources to enhance biochar properties and create friendly environmental substitute adsorbent in the removal of As contaminant using external magnet, and HMs (Pb 2+ , Cd 2+ , Cu 2+ , Zn 2+ , Ni 2+ ) [40,54]. Magnesium oxide nanoparticles on N-doped biochar is suitable for Pb adsorption and the removal of Cd 2+ and tetracycline in various environment obstructions (pH, natural organic matter, and metal ions), thus its suitability in the treatment of wastewater, natural water resources, and drinking water [149]. Similarly, modified and efficient zero-valent iron nanoparticles methods are cost effective.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…The research hotspots were transformed to competitive sorption between heavy metals (Deng et al 2017;Park et al 2016a), organic and heavy metals co-contamination removal (Frankel et al 2016;Zhou et al 2017b). An increasing research interest focused on the activated or modified biochar, which exhibited extremely high sorption efficiency for heavy metals (Deng et al 2018b;Ding et al 2016;Li et al 2017a;Ling et al 2017;Liu et al 2016;Niu et al 2017;Trakal et al 2016;Wu et al 2017b). Among the heavy metals, Cd immobilization by biochar was most studied, which could be seen from the relatively big ring in Fig.…”
Section: Heavy Metals' Immobilizationmentioning
confidence: 99%
“…The research about biochar remediation for heavy metals/metalloids contamination is well documented (Beesley and Marmiroli 2011; Cao et al 2009;Chen et al 2016;Lu et al 2012b;Qian et al 2017;Trakal et al 2014). With deeper understanding, the structures and surface properties of biochar have been modified with diverse methods, which deserves an increased attention globally (Chen et al 2011;Creamer et al 2018;Deng et al 2017Deng et al , 2018aLing et al 2017;Son et al 2018;Yao et al 2013;Zhang et al 2013a).…”
Section: Introductionmentioning
confidence: 99%